2017
DOI: 10.3389/fvets.2017.00053
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signaling of Progesterone, Growth Hormone, Wnt, and HER in Mammary Glands of Dogs, Rodents, and Humans: New Treatment Target Identification

Abstract: Mammary tumors are the most common form of neoplasia in the bitch. Female dogs are protected when they are spayed before the first estrus cycle, but this effect readily disappears and is already absent when dogs are spayed after the second heat. As the ovaries are removed during spaying, ovarian steroids are assumed to play an essential role in tumor development. The sensitivity toward tumor development is already present during early life, which may be caused by early mutations in stem cells during the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 159 publications
(191 reference statements)
0
15
0
Order By: Relevance
“…Therefore, our study adopts the methods of molecular biology affecting VEGF and wingless-type member 4 (WNT4) genes associated with bone calcium absorption. The WNT4 is key regulator in early embryogenesis; stem cells and WNT signaling are involved in the regulation of numerous processes of cell proliferation, differentiation and morphogenesis in humans and other species ( Timmermans-Sprang et al, 2017 ). The WNT4 is a secreted protein from osteoblasts and it has significant affect to inhibit bone resorption ( Hartmann and Tabin, 2000 ; Algandaby et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our study adopts the methods of molecular biology affecting VEGF and wingless-type member 4 (WNT4) genes associated with bone calcium absorption. The WNT4 is key regulator in early embryogenesis; stem cells and WNT signaling are involved in the regulation of numerous processes of cell proliferation, differentiation and morphogenesis in humans and other species ( Timmermans-Sprang et al, 2017 ). The WNT4 is a secreted protein from osteoblasts and it has significant affect to inhibit bone resorption ( Hartmann and Tabin, 2000 ; Algandaby et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Autocrine GH may have an even greater role in cancer development than endocrine GH (55). In mammary tissue GH1 expression has been found to be regulated by progesterone (56)(57)(58). GH belongs to the same family as prolactin (59), and in primates GH binds also to the PRLR, which presumably implicates all PRLR-mediated actions including mammary gland differentiation and lactation.…”
Section: Growth Hormone Physiology Gh Family and Structurementioning
confidence: 99%
“…23 However, the cell lines with high Wnt activity and rounded cell morphology had relatively high E-cadherin expression, 24 excluding the likelihood that loss of E-cadherin caused high canonical Wnt activity 25 and elevated β-catenin levels. [26][27][28] Further analysis by quantitative polymerase chain reaction (qPCR) of selected genes showed that the cell lines with high Wnt signalling overexpressed HER2,3 mRNA with LEF1, heat shock protein 90 (HSP90) and ras-like protein (RAC1), among others, and silenced phosphatase and tensin homologue (PTEN) mRNA expression. 20 The loss of PTEN expression in combination with an increased expression level of HER3, which promotes HER2-driven mammary tumour proliferation, 29 could indicate a highly activated PI3K/mammalian target of rapamycin (mTOR) pathway.…”
Section: In Human Breast Cancer Approximately 50% Of Clinical Samplesmentioning
confidence: 99%
“…In general, EMT, which is characterized by alterations in cell shape and loss of attachment to other cells and the extracellular matrix (ECM), is caused by loss of E‐cadherin expression . However, the cell lines with high Wnt activity and rounded cell morphology had relatively high E‐cadherin expression, excluding the likelihood that loss of E‐cadherin caused high canonical Wnt activity and elevated β‐catenin levels …”
Section: Introductionmentioning
confidence: 99%